Recycling carbon fiber composites using microwave irradiation: Reinforcement study of the recycled fiber in new composites. Issue 41 (8th July 2015) - Jiang, Long; Ulven, Chad A.; Gutschmidt, David; Anderson, Michael; Balo, Sloan; Lee, Mitchell; Vigness, Jacob
ABSTRACT With increasing use of carbon fiber reinforced polymer (CFRP) composites in transportation, sports, and many other industries, recycling of the scrap and end‐of‐life composites has presented both great challenges and opportunities. In this work, we report our study on reclaiming carbon fibers from CFRP using energy efficient microwave irradiation. Different irradiation conditions were used and the optimal conditions were determined based on the surface morphology of the recycled fiber. Polypropylene (PP) and Nylon, representing nonpolar and polar polymers, respectively, were reinforced using the recycled fiber through extrusion and injection molding. For comparison, PP and Nylon reinforced by virgin carbon fiber were also prepared using the same processing conditions. Tensile, flexural, and impact test results showed that, while both carbon fibers could improve these properties, they exhibited different reinforcing effects on the two polymers. The recycled fiber outperformed the virgin fiber in reinforcing PP whereas the virgin fiber performed better in Nylon. This was due to the differences in surface roughness, surface bonding, and fiber aspect ratio between the two fibers. This study shows the great potential of recycled carbon fiber and microwave irradiation as an effective recycling technique. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42658.